2020
DOI: 10.3390/cells9092104
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Characterization of Gut Microbiota-Derived Commensal Strains: Selection of Parabacteroides distasonis Strains Alleviating TNBS-Induced Colitis in Mice

Abstract: Alterations in the gut microbiota composition and diversity seem to play a role in the development of chronic diseases, including inflammatory bowel disease (IBD), leading to gut barrier disruption and induction of proinflammatory immune responses. This opens the door for the use of novel health-promoting bacteria. We selected five Parabacteroides distasonis strains isolated from human adult and neonates gut microbiota. We evaluated in vitro their immunomodulation capacities and their ability to reinforce the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
56
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 88 publications
11
56
1
1
Order By: Relevance
“…First, we verified that the bacteria were catalase-negative i.e., were not able to degrade H 2 O 2 when put in contact with it (data not shown). Second, the ability of the selected strains to modulate the H 2 O 2 -induced increase in paracellular permeability was evaluated using an in vitro epithelial barrier model as previously described [ 40 , 46 , 47 ]. As expected, the addition of H 2 O 2 reduced the TransEpithelial Electrical Resistance (TEER) indicating an increased permeability ( Figure 3 , H 2 O 2 ) reflecting the sensitization of the cell monolayers in the control.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…First, we verified that the bacteria were catalase-negative i.e., were not able to degrade H 2 O 2 when put in contact with it (data not shown). Second, the ability of the selected strains to modulate the H 2 O 2 -induced increase in paracellular permeability was evaluated using an in vitro epithelial barrier model as previously described [ 40 , 46 , 47 ]. As expected, the addition of H 2 O 2 reduced the TransEpithelial Electrical Resistance (TEER) indicating an increased permeability ( Figure 3 , H 2 O 2 ) reflecting the sensitization of the cell monolayers in the control.…”
Section: Resultsmentioning
confidence: 99%
“…The bacterial survival to gastric stress was strain-dependent and only P. distasonis PF-BaE7 among the seven strains combining several probiotic functions was tolerant to that stress condition. However, we previously showed that adding sodium bicarbonate to the bacterial suspensions to neutralize the gastric pH, improved the strain survival during the in vitro stress assay (data not shown) and could also allow significant protection against intestinal inflammation after in vivo administration of gastric-stress sensitive strains [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, flagellin also induces IRAK3 expression in cultured intestinal epithelial cells, which is associated with tolerance induction [ 80 ]. Microbiota-induced strengthening of the gut barrier is a mechanism that can influence different pathological processes in the gut and liver and may even be employed in fundamental processes, such as age-related “leaky gut” [ 81 , 82 , 83 ]. Therefore, we analyzed ileal and colonic expression of the flagellin sensor Tlr5 , the negative regulator of TLR signaling Irak3 , the gene for tight junction protein ZO-1 ( Tjp1 ), Muc13, and a set of anti-microbial peptides, including the murine functional orthologue of human beta-defensin 2, Defb4 [ 84 ].…”
Section: Discussionmentioning
confidence: 99%